2001
DOI: 10.1034/j.1600-079x.2001.310207.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin versus vitamin E as protective treatment against oxidative stress after extra‐hepatic bile duct ligation in rats

Abstract: The aims of the present study were first to compare the effects of melatonin and vitamin E on the cholestasis syndrome and their protective effect on liver injury, and second, to evaluate the activity of antioxidant enzymes after treatment with these antioxidant drugs. Cholestasis was achieved in adult male Wistar rats by double ligature and section of the extra-hepatic biliary duct. Hepatic and plasma oxidative stress markers were evaluated by changes in the amount of lipid peroxides, measured as malondialdeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 33 publications
7
105
2
3
Order By: Relevance
“…It was reported that melatonin can reduce free radical damage by elevating GPx activation [11,39] . Montilla et al [25] reported that acute ligation of the bile duct is accompanied with decreased GSH levels both in plasma and in liver, as well as significantly reduced antioxidant enzyme activities. Treatment with melatonin is associated with a significant recovery of anti-oxidative enzymes such as GPx [25] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that melatonin can reduce free radical damage by elevating GPx activation [11,39] . Montilla et al [25] reported that acute ligation of the bile duct is accompanied with decreased GSH levels both in plasma and in liver, as well as significantly reduced antioxidant enzyme activities. Treatment with melatonin is associated with a significant recovery of anti-oxidative enzymes such as GPx [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Montilla et al [25] reported that acute ligation of the bile duct is accompanied with decreased GSH levels both in plasma and in liver, as well as significantly reduced antioxidant enzyme activities. Treatment with melatonin is associated with a significant recovery of anti-oxidative enzymes such as GPx [25] . Tahan et al [12] found that melatonin can restore GPx activity in a rat liver fibrosis model induced by a 14-d dimethylnitrosamine regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-standing cholestasis could lead to portal hypertension, hepatic dysfunction, and eventually hepatic cirrhosis (Parola et al, 1996). The pathogenesis is uncertain, but several studies reported that free radicals may play a role in cholestatic liver injury (Montilla et al, 2001;Pastor et al, 1997). Bile acids enhanced the release of free radicals from activated polymorphonuclear and inflammatory cells in cholestatic liver lesions (Dahm et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic fibrosis, the main complication of chronic liver disease, is usually initiated by hepatocyte damage, leading to recruitment of inflammatory cells and platelets, activation of Kuppfer cells and subsequent release of cytokines and growth factors (1). It is known that increased concentration of bile acids induce lipid peroxides, probably related to the stimulation of phagocytic activity in the polymorphonuclear leukocytes and inflammatory cells, which are present after biliary tract obstruction and enhance the tissue injury (2,3). Several clinical and experimental studies have shown that oxygen free radicals have a role in the pathogenesis of tissue injury in obstructive jaundice (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%